Case Report: Favorable outcome of allogeneic hematopoietic stem cell transplantation in SARSCoV2 positive recipient, risk-benefit balance between infection and leukemia - Oltolini, Chiara; Acerbis, Andrea; Orofino, Giorgio; Racca, Sara; Noviello, Maddalena; Dispinseri, Stefania; Clementi, Nicola; Piemontese, Simona; Xue, Elisabetta; Giglio, Fabio; Lupo Stanghellini, Maria Teresa; Diral, Elisa; et al. (Frontiers in Immunology, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) in SARS-CoV-2 positive candidates is usually delayed until the clinical resolution of the infection’s symptoms and a negative nasopharyngeal molecular test. However, prolonged SARS-CoV-2 positivity has been frequently observed in haematological malignancies, thus representing a challenge for the timing of transplant procedures. Here, we report on the case of a 34-year-old patient with recent pauci-symptomatic COVID-19 undergoing transplant for high-risk acute B-lymphoblastic leukemia before achieving viral clearance. Shortly before their scheduled allogeneic HSCT from a matched unrelated donor, the patient developed mild Omicron BA.5 infection receiving nirmatrelvir/ritonavir with fever resolution within 72 hours. Twenty-three days after COVID-19 diagnosis, because of increasing minimal residual disease values in the context of high-risk refractory leukemia and clinical resolution of SARS-2-CoV infection with reduction of viral load at surveillance nasopharyngeal swabs, it was decided not to delay further allo-HSCT. During myelo-ablative conditioning, the nasopharyngeal SARS-CoV-2 viral load increased while the patient remained asymptomatic. Consequently, two days before the transplant, intra-muscular tixagevimab/cilgavimab 300/300 mg and a 3-day course of intravenous remdesivir were administered. During the pre-engraftment phase, veno-occlusive disease (VOD) occurred at day +13, requiring defibrotide treatment to obtain a slow but complete recovery. The post-engraftment phase was characterized by mild COVID-19 at day +23 (cough, rhino-conjunctivitis, fever) that spontaneously resolved, achieving viral clearance at day +28. At day +32, she experienced grade I acute graft-versus host disease (a-GVHD, skin grade II) treated with steroids and photo-apheresis, without further complications during follow-up until day +180. Addressing the issue of allo-HSCT timing in patients recovering from SARS-CoV-2 infection with high-risk malignant diseases is challenging because of 1] the high risk of COVID-19 clinical progression, 2] the impact of transplant delay on leukemia prognosis and 3] the occurrence of endothelial complications such as VOD, a-GVHD, and transplant associated thrombotic micro-angiopathy. Our report describes the favourable outcome of allo-HSCT in a recipient with active SARS-CoV2 infection and high-risk leukemia thanks to timely anti-SARS-CoV-2 preventive therapies and prompt management of transplant-related complications.